A Free‐Blockage Controlled Release System Based on the Hydrophobic/Hydrophilic Conversion of Mesoporous Silica Nanopores. Issue 6 (11th December 2014) - Wang, Wenqian; Chen, Linfeng; Xu, Li‐ping; Du, Hongwu; Wen, Yongqiang; Song, Yanlin; Zhang, Xueji
Abstract A pH‐responsive free‐blockage release system was achieved through controlling the hydrophobic/hydrophilic conversion of mesoporous silica nanopores. This system further presented pulsatile release with changing pH values between 4.0 and 7.0 for several cycles. This free‐blockage release system could also release antitumor agents to induce cell death after infecting tumor cells and could have the ability of continuous infection to tumor cells with high drug‐delivery efficiency and few side effects.